Analisis Pelanggaran Hak Asasi Manusia Yang Terjadi Dalam Kelompok Kriminal Bersenjata Papua Melibatkan Anggota Tentara Nasional Indonesia Angkatan Darat - Irwan Triadi; Nurrachma Maharani; Jhessica Hawana; Anatasia Lamminar; Diva Salsabila Ferdiansyah; Nafisa Verlee (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Law has an important role in the Indonesian state system which refers to the principle of the rule of law, where both the government and citizens must comply with applicable laws. Law in Indonesia covers various fields and has a crucial role in creating social and economic justice and protecting human rights. Laws also reflect a society's values, culture, and history. Apart from that, this research will discuss the chronology of cases and juridical reflections regarding terrorism crimes in Papua as well as the state's responsibility regarding human rights violations by the Armed Criminal Group (KKB) in Papua. This research aims to further understand the chronology of cases and forms of juridical reflection from a legal perspective in Indonesia, the actions taken by the Indonesian National Army to overcome terrorist crimes in Papua, and the state's responsibility regarding human rights violations by the Papuan Armed Criminal Group. This research method uses qualitative methods related to journals and related literature. The results of this research show the need for efforts to achieve peace in Papua, proportional action in protecting Papuans, and attention to decision-making mechanisms in the involvement of the Indonesian National Army in countering terrorism. The suggestions given include expanding cooperation with local communities, evaluating the Papua Special Autonomy Law, a holistic approach in dealing with terrorism, synergy between related institutions, and fair and transparent law enforcement.